2013
DOI: 10.1111/pace.12066
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hemodialysis on the Dispersion of Ventricular Repolarization

Abstract: HD induces an increase in novel markers of spatial dispersion of ventricular repolarization. Whether the assessment of these indexes of heterogeneity of repolarization at baseline or their change during HD has a prognostic value with regard to future untoward events, remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
7
0
2
Order By: Relevance
“…found that both intervals were increased in duration after a single hemodialysis session. 17 Prolongation of TpTe or TpTe/QT was not associated with changes in electrolytes, which suggest that the changes in TpTe were not related to the large electrolyte shifts that routinely occur in patients receiving hemodialysis. Other authors have examined the effect of hemodialysis on QT dispersion, which is another marker of the dispersion of ventricular repolarization.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…found that both intervals were increased in duration after a single hemodialysis session. 17 Prolongation of TpTe or TpTe/QT was not associated with changes in electrolytes, which suggest that the changes in TpTe were not related to the large electrolyte shifts that routinely occur in patients receiving hemodialysis. Other authors have examined the effect of hemodialysis on QT dispersion, which is another marker of the dispersion of ventricular repolarization.…”
Section: Discussionmentioning
confidence: 95%
“… 15 , 16 Although hemodialysis has been shown to prolong the TpTe interval, no study have examined the predictive ability of a baseline TpTe interval in patients with ESRD. 17 We hypothesized that TpTe and TpTe/QT are independent risk factors for SCD in ESRD. The aim of this study was to assess the prognostic value of TpTe and TpTe/QT for SCD in ESRD patients, independent of the mechanism for prolongation of the TpTe interval.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 ], Tp-e was reported to be increased in the patients with ESRD, compared to the controls. In another study reporting no changes in QTc interval and QT dispersion, it was reported that Tp-e interval and Tp-e/QT ratio increased after hemodialysis and also speculated that hemodialysis induced ventricular arrythmias [ 40 ]. Because the number of studies is too limited, we consider that no speculation can be made on Tp-e interval and Tp-e/QT ratio in the patients with CKD and that these entities should be supported with novel studies with larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of these deaths are likely triggered by fatal arrhythmia (ventricular tachycardia/fibrillation), superimposed on susceptible substrates with myocardial ischemia or systolic dysfunction ( Wang et al, 2010 ). Furthermore, electrocardiographic alterations, such as QTc interval alterations and repolarization dispersions, have been reported to be pathogenic in ventricular arrhythmia among chronic hemodialysis patients, serving as potential risk factors for SCD ( Kalantzi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%